The Use of Reader-Response Theory to Teach Reading Narrrative Text for Tenth Graders of Senior High School (RETAIN, 2018)
Abstract This research was aimed to describe the use of reader-response theory to teach reading narrative text and to describe the students’ responses toward the text. This research was conducted qualitatively. This research used some instruments, which are observation checklist, field notes, transcription, and document. The observation checklist and the field notes were used to know how the reader-response theory was used to teach reading narrative text in the classroom, which was conducted in three meetings. In addition, to know the type of the students responses toward the text during the reading process based on the reader-response theory, the researcher used the transcription and the document of the students’ works. From this research, it could be said that the reader-response theory was used in the form of spoken and written activities. The teacher also had applied the Engaging, Describing, Conceiving, Explaining, Connecting, Interpreting, and Judging strategies during the teaching and lerning process. Furthermore, the students made Interpretive, Affective, Reflective, Associative, and Queries response toward the text when they were involved in the RRT-based reading process. Keywords: Reading, Narrative Text, Reader-Response Theory. Abstrak Penelitian ini bertujuan untuk mendeskripsikan penggunaan reader-response theory untuk membaca teks naratif dan untuk mendeskripsikan tanggapan siswa terhadap teks tersebut. Penelitian ini dilakukan secara kualitatif. Penelitian ini menggunakan beberapa instrumen, seperti daftar kriteria pengamatan, catatan lapangan, transkripsi, dan dokumen. Daftar kriteria pengamatan dan catatan lapangan digunakan untuk mengetahui bagaimana reader-response theory digunakan dalam pembelajaran membaca teks naratif di kelas, yang dilaksanakan dalam tiga pertemuan. Sebagai tambahan, untuk mengetahui jenis tanggapan siswa terhadap teks selama proses membaca yang berdasar pada reader-response theory dilaksanakan, peneliti menggunakan transkripsi dan dokumen dari lembar kerja siswa. Dari penelitian ini, dapat dikatakan bahwa reader-response theory diterapkan dalam bentuk aktivitas-aktivitas oral dan tulis. Guru juga telah mengaplikasikan strategi Menarik, Menggambarkan, Memahami, Menjelaskan, Menghubungkan, Menginterpretasikan, dan Menilai selama proses belajar-mengajar. Selain itu, para siswa memberi tanggapan Interpretatif, Afektif, Reflektif, Asosiatif, dan tanggapan yang berupa pertanyaan terhadap teks ketika mereka terlibat dalam proses membaca yang berdasar pada reader-response theory. Kata kunci: Membaca, Teks Naratif, Reader-Response Theory.